THE IMPACT OF INDOOR CYCLING TRAINING ON HEMODYNAMIC PARAMETERS OF THE LEFT VENTRICLE OF MEN WITH ISCHAEMIC HEART DISEASE OR AFTER MYOCARDIAL INFARCTION - D. D. Gloc; Z. Nowak (Российский кардиологический журнал)
Aim. Younger age of the cardiac patients somehow necessitates the use of modern forms  of physical  training,  which become alternative  and  interesting  means  to provide effective rehabilitation. One such form is endurance Indoor Cycling training. In the present study attempts to determine  the impact of 1-month Indoor Cycling training on  hemodynamic  left ventricle parameters of men  with ischemic  heart disease or after myocardial infarction were made.Material and methods. The study group consisted of 50 men under the model A of the 2nd phase  of cardiac rehabilitation (20 men of the Indoor Cycling group, IC, 20 men  rehabilitated  accordingly  to  the  recommendations  of  the  Polish  Cardiac Society — a standard group, ST and 10 people who did not participate in any cardiac rehabilitation program  — a control group, C). The average  age of all patients  was 56,60±8,25  years, the average left ventricular ejection fraction was 56%±4,00. Results. Echocardiogram   did  not  show  significant  changes after  1-month  of training in both groups undergoing comprehensive cardiac rehabilitation. Paralleled to the preliminary study in the group of patients  who refused  to participate  in the cardiac   rehabilitation,   results   showed   a  reduction   in  all  echocardiographic parameters, including a significant decrease in the  left ventricular end  diastolic diameter (52,80 vs 50,50 mm) and volume (134,85 vs 121,88 ml; both variables at p<0,001),  as well as in the left ventricular mass (239,46 vs 208,61 g; p=0,002) and the left ventricular mass index (123,52 vs 107,61 g/m2; p=0,001).Conclusion. No negative influence of the Indoor Cycling training on morphological parameters of the left ventricle was observed. Indoor Cycling training in the second phase  of cardiac  rehabilitation  in patients  with ischemic  heart  disease or after myocardial infarction is a safe form of therapy and therefore  may be an interesting alternative method to the classic bicycle ergometer exercise in the stage of an early cardiac rehabilitation.